A Review of Population-Based Studies on Hypertension in Ghana - Addo, J (Ghana Medical Association, 2012)
BACKGROUND: Hypertension is becoming a common health problem worldwide with increasing life expectancy and increasing prevalence of risk factors. Epidemiological data on hypertension in Ghana is necessary to guide policy and develop effective interventions. METHODS: A review of population-based studies on hypertension in Ghana was conducted by a search of the PUBMED database, supplemented by a manual search of bibliographies of the identified articles and through the Ghana Medical Journal. A single reviewer extracted data using standard data collection forms. RESULTS: Eleven studies published on hypertension with surveys conducted between 1973 and 2009 were identified. The prevalence of hypertension was higher in urban than rural areas in studies that covered both types of area and increased with increasing age (prevalence ranging from 19.3% in rural to 54.6% in urban areas). Factors associated with high blood pressure included increasing body mass index, increased salt consumption, family history of hypertension and excessive alcohol intake. The levels of hypertension detection, treatment and control were generally low (control rates ranged from 1.7% to 12.7%). CONCLUSION: An increased burden of hypertension should be expected in Ghana as life expectancy increases and with rapid urbanisation. Without adequate detection and control, this will translate into a higher incidence of stroke and other adverse health outcomes for which hypertension is an established risk factor. Prevention and control of hypertension in Ghana is thus imperative and any delays in instituting preventive measures would most likely pose a greater challenge on the already overburdened health system.